Identification of digital innovation service performance indicators influencing UAE judicial system - Al Katheeri, Hamad; Kudus, Norliah (Tropical Scientific Journal, 2024)
Objective: The global economic crisis has had a profound impact on youth unemployment, affecting young job seekers both directly and indirectly. As a result, they are confronted with limited job opportunities, which, in turn, elevates the risk of long-term unemployment. Furthermore, this crisis has created significant barriers to achieving financial independence through secure, stable employment. Therefore, this paper aims to examine the underlying causative factor of youth unemployment that have been exacerbated by the global economic crisis. Research Method: In this study, a questionnaire survey was conducted to collect the perspectives of both employees at the UAE Ministry of Labor and Productivity and young job seekers. The questionnaire was designed to investigate the underlying causes of youth unemployment, especially in light of the global economic crisis. Respondents were asked to assess the significance of various factors from their standpoint, using a 5-point Likert scale. Data collected from the survey was analysed descriptively. Findings: It was found that the top position is ER6, representing Policies and Support Measures, with a leading mean value of 4.568. Following closely in the second rank is ITT4, addressing Effects on the labour force, with a mean value of 4.485. The third rank is held by ITT2, associated with Job losses within affected sectors, boasting a mean value of 4.448. The last rank is occupied by ER3, denoting Long-term scarring effects, with a mean value of 3.277. Originality: Hopefully, this study able to assist in handling youth unemployment, especially during the global economic crisis. Keywords: global economic crisis, youth unemployment, causative factors